2013
DOI: 10.1148/radiol.13120197
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic CT Angiography after Abdominal Aortic Endovascular Aneurysm Repair: Influence of Enhancement Patterns and Optimal Bolus Timing on Endoleak Detection

Abstract: Dynamic CT angiography revealed that the peak enhancement of endoleaks is significantly different than that of the aorta and that endoleaks may not be adequately evaluated with conventional biphasic CT protocols. The use of dynamic CT angiography is associated with a significantly increased detection rate of endoleaks compared with the detection rates at the time points of conventional biphasic CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…However, a radiation dose of retrospectively triggered or gated CTA is much higher in comparison to that of conventional CTA. 49,50 The use of dual source technology and the high pitch that can be achieved with this technique (up to 3.4) may overcome the need for ECG triggering and thus reduce the radiation dose, without loss of diagnostic accuracy. 51 Post-processing of axial CT data is possible using multiplanar reformation (MPR), maximal intensity projection and volume rendering technique.…”
Section: Computed Tomography Angiographymentioning
confidence: 99%
“…However, a radiation dose of retrospectively triggered or gated CTA is much higher in comparison to that of conventional CTA. 49,50 The use of dual source technology and the high pitch that can be achieved with this technique (up to 3.4) may overcome the need for ECG triggering and thus reduce the radiation dose, without loss of diagnostic accuracy. 51 Post-processing of axial CT data is possible using multiplanar reformation (MPR), maximal intensity projection and volume rendering technique.…”
Section: Computed Tomography Angiographymentioning
confidence: 99%
“…The percentage of endoleaks after EVAR is generally reported to be 20-30 %, but endoleaks may be more common than previously believed [11,12]. That is, completion aortography sometimes fails to detect the presence of endoleaks.…”
Section: Discussionmentioning
confidence: 98%
“…Studies of temporal enhancement patterns in the aneurysm sac after EVAR have shown that peak enhancement of endoleaks is variable and may be missed by biphasic CT protocols with fixed contrast timing. 12 For early-dynamic PET/CT and PET angiography, the dynamic dataset is reconstructed retrospectively and can be adapted to the clinical query and individual circulation times. Performed in addition to a standard PET/CT done to evaluate prosthesis inflammation or other questions, no separate radioactive tracer application is necessary.…”
Section: Discussionmentioning
confidence: 99%